Assessing and Enhancing Emotional Intelligence among Nigerian Librarians - Idowu, Adetoun Omolola; Adegboyega, Lateef Omotosho (Universitas Pendidikan Indonesia, 2020)
ABSTRACT: The democratization process in Nigeria has been dismally slow owing to issue of leadership in Nigeria, especially among the librarians. Researchers have attributed this prevalent tendency of the Nigerian librarians not being able to manage library failures and successes to inadequacies of emotional intelligence requisite for career progression and professional self-actualization. There is dearth of research in the area of assessing and enhancing emotional intelligence among Nigerian librarians. Attempts made to uncover related studies in this area have proved abortive. It is anticipated that the position of this paper will provide baseline information for research as to how emotional intelligence affects leadership styles in the library organisation. By using the qualitative approaches and literature review, this study tries to elaborate key concepts of leadership and its relationship with the Nigerian librarians, such as: Concept of Emotional Intelligence; Emotional Intelligence and Leadership; Leadership and Leadership Style; the Transformational-Transactional Leadership Style Theory by J.M. Burns was Used to Explain the Concept of Leadership Style; and Relevance of J.M. Burns Theory to this Study. KEY WORD: Assessing; Enhancing; Emotional Intelligence; Nigerian Librarians.Â ABSTRAKSI: â€œMenilai dan Meningkatkan Kecerdasan Emosional diantara Pustakawan Nigeriaâ€. Proses demokratisasi di Nigeria berjalan sangat lambat karena isu kepemimpinan di Nigeria, khususnya di kalangan pustakawan. Para peneliti telah mengaitkan kecenderungan umum dari pustakawan Nigeria yang tidak mampu mengelola kegagalan dan keberhasilan perpustakaan ini dengan ketidakcukupan kecerdasan emosional yang diperlukan untuk kemajuan karier dan aktualisasi diri profesional. Ada kelangkaan penelitian di bidang menilai dan meningkatkan kecerdasan emosional diantara pustakawan Nigeria. Upaya yang dilakukan untuk mengungkap studi terkait di bidang ini terbukti gagal. Posisi makalah ini diantisipasi akan memberikan informasi dasar untuk penelitian tentang bagaimana kecerdasan emosional mempengaruhi gaya kepemimpinan dalam organisasi perpustakaan. Dengan menggunakan pendekatan kualitatif dan kajian pustaka, penelitian ini mencoba menguraikan konsep-konsep kunci kepemimpinan dan hubungannya dengan pustakawan Nigeria, seperti: Konsep Kecerdasan Emosional; Kecerdasan Emosional dan Kepemimpinan; Kepemimpinan dan Gaya Kepemimpinan; Teori Gaya Kepemimpinan Transformasional-Transaksional oleh J.M. Burns Digunakan untuk Menjelaskan Konsep Gaya Kepemimpinan; serta Relevansi Teori J.M. Burns dengan Studi ini.KATA KUNCI: Menilai; Meningkatkan; Kecerdasan Emosional; Pustakawan Nigeria. Â Â About the Authors: Prof. Adetoun Omolola Idowu, Ph.D. is a Lecturer at the Department of Library Science, Faculty of Communication and Information Sciences, UNILORIN (University of Ilorin) in Ilorin, Nigeria. Lateef Omotosho Adegboyega, Ph.D. is a Lecturer at the Department of Counsellor Education, Faculty of Education, UNILORIN in Ilorin, Nigeria. For academic interests, the Authors are able to be contacted via e-mail address at: adetouni@yahoo.com and adegboyega.lo@unilorin.edu.ngSuggested Citation: Idowu, Adetoun Omolola Lateef Omotosho Adegboyega. (2020). â€œAssessing and Enhancing Emotional Intelligence among Nigerian Librariansâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 5(2), September, pp.101-116. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (July 27, 2020); Revised (Agustus 30, 2020); and Published (September 30, 2020).